Monthly changes of night heat islands analysis in Isfahan County in the last two decades using the multi-temporal products of the MODIS sensor - Mostafa Tahani Yazdly; Sayyed Mohammad Hosseini; Farahnaz Khoramabadi; Mohammad Mohtaram (علوم محیطی)
Introduction: In recent decades, along with the physical development of cities and population increase due to immigration, heat islands, which are mainly the result of human made activities, have gained significant importance. So, the reduction of vegetation cover, the high consumption of fossil fuels, the emission of greenhouse gases and the use of inappropriate materials in urban construction have created the microclimate of a heat island above the metropolis of the world. Finally, it causes an increase in the land surface temperature, atmospheric stability, persistence and stabilization of pollutants and an increase in respiratory diseases. Today, by using remote sensing methods and using digital satellite images, it is possible to examine the land surface temperature with high accuracy and in a short period using MODIS sensors and Terra satellite images. Therefore, the main objective of the current research was to analyze the temporal and spatial variations of heat islands of Isfahan using the principal component analysis method. With this technique, it is possible to identify the seasons and months when the land surface temperature and the heat island increased. Material and Methods: In this regard, the present research considered analyzing the temporal and spatial variations of this phenomenon in Isfahan during a period of 20 years (from 2000 to 2020 AD). To achieve this purpose, the land surface temperature (LST) data extracted by MODIS sensor and Terra satellite was used. These data are available for the whole world with a time resolution of 8 days and a spatial resolution of 1x1 km in a sinusoidal grid with dimensions of 1200x1200 km. Therefore, for Isfahan, 913 images were extracted from the MODIS sensor. Then, with the principal component analysis (PCA) method, the seasons and months that have the most influence on the occurrence of heat islands were identified and in order to analyze the trend of this phenomenon, the Mann-Kendall and the Kolmogorov-Smirnov tests were used.Results and Discussion: The findings of the research indicated that the land surface temperature in the last 20 years in Isfahan had an increasing trend with a rate of 4%. However, this trend in the population and urban centers has been completely different from the surrounding areas of Isfahan. In terms of spatial distribution, the highest occurrence of heat islands has been registered in the eastern and southeastern parts (including Hassan Abad and Jolgeh) due to proximity to the hot deserts of Kavir-Lout, proximity to Sepiddasht, Varzaneh, Shahrak Ramsheh industrial towns and changes in the land use of agricultural to industrial and residential. also in the North-West region (including Mahmudabad and Isfahan city) due to the increase in man-made heating caused by the increase in the consumption of fossil fuels, the growth of residential, industrial and commercial units, temperature has risen. In addition, the results showed that the intensity of the heat island in winter is higher than in summer, and the most intense time of its occurrence was recorded in January and the least in November.Conclusion: Isfahan is integrally affected by global climate conditions, but depending on the geographical location of each part of this province, the land surface temperature and the occurrence of heat islands are different, so that, eastern and central parts, adjacent to Kavir-Lout and close to industrial towns, have an increasing trend. Moreover, the southern parts have a decreasing rate of temperature and heat islands due to less urban population, larger agricultural lands and more vegetation. The increase in urbanization, migration, and the increase in fossil fuel consumption, the decrease in vegetation, the aggravation of drought, and the change in land use have a fundamental role in increasing the occurrence of this phenomenon.